Pengaruh Likuiditas, Leverage, Sales Growth dan Ukuran Perusahaan Terhadap Financial Distress Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2015-2017 - Yola Amanda; Abel Tasman (Jurnal Ecogen, 2019)
Financial distress is the stage of decreasing the company's financial condition that occurs before the company goes bankrupt. This research is conducted to see the effect of liquidity, leverage, sales growth and company size on financial distress of manufacturing companies listed on the Indonesia Stock Exchange. The population in this study are all Manufacturing Companies listed on the Indonesia Stock Exchange for the period 2015-2017. The sample selection is determined by purposive sampling. This research uses logistic regression as the data analysis technique. The results of the this research state that (1) liquidity has a negative and no significant effect on financial distress of manufacturing companies, (2) leverage has a positive and significant effect on  financial distress of manufacturing companies, (3) sales growth has a negative and significant effect on the financial distress of manufacturing companies, (4) company size has a negative and no significant effect on financial distress of manufacturing companies. The suggestion of this research are, (1) for the next researcher, it is recommended to be able to add the period of research and to use other indicators related to the factors that influence financial distress. (2) for the management, it is better to be aware of the company's financial condition. (3) for investors and creditors to be able to seek information in advance about the company's financial condition before deciding to invest and provide loans to a company.Keywords: financial distress, likuiditas, leverage, sales growth, firm size